2008
DOI: 10.1038/onc.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

p53 target gene AEN is a nuclear exonuclease required for p53-dependent apoptosis

Abstract: DNA degradation is one of the biochemical hallmarks detected in apoptotic cells, and several nucleases have been reported to function cooperatively in this process. It has also been suggested that different sets of nucleases are activated by different stimuli, and induce distinct patterns of DNA degradation. Here we report that apoptosisenhancing nuclease (AEN) is a novel direct target gene of p53. AEN is induced by p53 with various DNA damage, and its expression is regulated by the phosphorylation status of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 41 publications
3
68
0
Order By: Relevance
“…CASP3 initiates apoptosis by cleaving cellular substrates, which results in shrinkage of cells and degradation of the contents of cells (Jaeschke et al, 2012). Apoptosis enhancing nuclease (APOPEN) is an exonuclease that is induced by p53 following DNA damage and digests double-stranded DNA to form single-stranded DNA and amplifies DNA signals related to damage to DNA, which results in enhancement of apoptosis (Kawase et al, 2008). Apoptosis inhibitor 5 (APOPIN5) is an inhibitor of apoptosis that prevents fragmentation of DNA after activation by CASP3 (Morris et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CASP3 initiates apoptosis by cleaving cellular substrates, which results in shrinkage of cells and degradation of the contents of cells (Jaeschke et al, 2012). Apoptosis enhancing nuclease (APOPEN) is an exonuclease that is induced by p53 following DNA damage and digests double-stranded DNA to form single-stranded DNA and amplifies DNA signals related to damage to DNA, which results in enhancement of apoptosis (Kawase et al, 2008). Apoptosis inhibitor 5 (APOPIN5) is an inhibitor of apoptosis that prevents fragmentation of DNA after activation by CASP3 (Morris et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that p53-72P was less phosphorylated at Ser-6 compared with p53-72R under all conditions studied, and TGF-␤-dependent and -independent induction of p21 was attenuated in p53-72P-expressing cells. Previously, we have shown that phosphorylation of Ser-6 does not affect binding of p53 to p21 promoter (8). Therefore, Ser-6 may affect other aspects of p21 promoter activation, such as cofactor recruitment to the promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Seven serines, Ser-6, -9, -15, -20, -33, -37, and -46, within the transactivation domain undergo phosphorylation (6). Phosphorylation of each residue has been reported to have specific physiological significance; for example, phosphorylation of Ser-15 or -46 modifies the transactivation ability of p53 (7)(8)(9), whereas Ser-20 is required for p53 protein stability (10). When not phosphorylated, p53 is actively degraded by the 26 S proteasome pathway by interacting with a ring finger ubiquitin E3 ligase, Mdm2.…”
mentioning
confidence: 99%
“…3B). Among them are AEN, which encodes a nuclear exonuclease required for p53-dependent apoptosis (24) and was recently linked to p53-dependent autophagy in response to DNA damage induction (25); LRDD, whose protein product interacts with several death domain proteins, such as Fas-associated death domain (FADD) and mitogenactivated protein kinase-activating death domain-containing protein (MADD) Fig. 2.…”
Section: Transcriptome Dynamics After X-irradiationmentioning
confidence: 99%